Fact or Fraud? - Campbell, Ian (Journal of Telecommunications and the Digital Economy, 2017)
Epidemic - a widespread occurrence of an infectious disease in a community at a particular time - outbreak, scourge, plague.About 1976 concerns emerged in Australia about the potential for new technologies to seriously reduce employment. The debate reached a peak in 1978 when industrial action taken by the Australian Telecommunications Employees Association (ATEA) threatened to shut down the Australian telecommunications network.From 1975 growth in calls to the directory assistance service rocketed as did the related operating costs. To maintain the quality of customer service and contain operating costs, Telecom began to deploy a nation-wide computer- based directory assistance system (DAS/C) from 1982. In 1983 an unexpected medical syndrome arose in one of Telecom's directory assistance centres.Over the next three years, the syndrome rapidly spread through other directory assistance centres, other areas of Telecom and some areas of the public service. The media, academia, legal practitioners and others attracted to the "problem" generally accepted the union view that the DAS/C system was the cause and the syndrome was labelled Repetitive Strain Injury (RSI). Medical costs and compensation claims mounted reaching $130 million in 1989.While RSI has become a well-known syndrome over the last 40 years, no outbreaks of the extent and severity experienced in Telecom appear to have been recorded over that period anywhere in the world. There still appears to be little scientific evidence of the link between the injury of the reported scale and the workplace.This is the story of the rise of the RSI phenomena in Telecom over the period 1983-86.